Kebutuhan dan Struktur Kelembagaan Rantai Pasok Buah Manggis: Studi Kasus Rantai Pasok di Kabupaten Bogor - Astuti, Retno; Marimin, Marimin; Poerwanto, Roedhy; Machfud, Machfud; Arkeman, Yandra (Universitas Prasetiya Mulya, 2010)
Mangosteen (Garcinia mangostana L.) is the highly demanded fruit for export commodity from Indonesia. The biggest mangosteen production center in Indonesia is West Java Province that includes Purwakarta, Subang, Bogor, and Tasikmalaya contributing 90% of mangosteen production in West Java Province and 29% of national mangosteen production. The activities of mangosteen production in West Java Province have not been efficient yet, so the potential source of the fruit in West Java Province is not efficient enough to compete internationally. In order to have competitive advantages, supply chain management in mangosteen business was initiated in Bogor district in 2007 which integrated processes from receiving raw material to selling finished products. Needs identification and institutional structure in emerging supply chain of mangosteen in Bogor District were necessary to be carried out to improve the efficiency and effectiveness of the chain to achieve its objectives. In running its business processes, the member of the chain will be linked between each other. Supply chain needs will also be linked with each other. In this study, Intepretative Structural Modeling was used to describe the relationship between needs of the chain and relationships among the institutions in the chain.